Numerical Simulation of Sudden Gas Pipeline Leakage in Urban Block. (May 2017) - Yang, Jingjing; Zhang, Jihao; Mei, Shuojun; Di Liu,; Zhao, Fuyun
Abstract: Nowadays, the leakage model of low-pressure natural gas pipeline under the atmospheric environment has been established with the leak rate decrease with time. The Fluent software is used to simulate the concentration distribution and velocity distribution of gas among buildings at different time after the leakage, the influence of aspect ratio, distance between buildings is considered to maximally simulate the impact of external environment on natural gas leakage and diffusion. Finally we obtained the diffusion trend and concentration distribution under different conditions of gas leakage, so that rescue workers can acquire the transport status and influence of leaked gas in blocks in a short time, and provide a theory foundation for accident rescue.